Basic researchCyclic tensile stretch modulates osteogenic differentiation of adipose-derived stem cells via the BMP-2 pathway - Yang, Xingmei; Gong, Ping; Lin, Yunfeng; Zhang, Lirong; Li, Xiaoyu; Yuan, Quan; Tan, Zhen; Wang, Yongyue; Man, Yi; Tang, Hua (Archives of Medical Science, 2010)
Introduction: Mechanical forces play critical roles in the development and remodelling process of bone. As an alternative cell source for bone engineering, adipose-derived stem cells (ASCs) should be fully investigated for their responses to mechanical stress and the mechanisms responsible for osteogenic induction in response to mechanical signals. Material and methods: We hypothesized that appropriate application of uniaxial cyclic tensile strain to ASCs could increase bone morphogenetic protein-2 (BMP-2) expression and improve osteogenesis of ASCs. To test our hypothesis, ASCs from the same flask of the same donor were subjected to tensile strain with different patterns in order to eliminate the difference of donor site and passage. After surface markers investigation, the osteo-induced ASCs were subjected to uniaxial cyclic tensile stretch with the following two loading patterns: long duration continuous pattern (6 h, 1 HZ, 2000 με) and short duration consecutive pattern (17 min every day for 10 consecutive days, 1 HZ, 2000με ). Then osteogenic related genes were analysed by real-time PCR. Results: The ASCs were positive for the markers STRO-1, CD90 and CD44 and negative for CD34. Cyclic tensile strain of 6 continuous h’ duration significantly increased gene expressions of BMP-2 and Runx2, and depressed OCN mRNA expression. In contrast, mechanical loading of 17 min every day did not significantly affect gene expression of BMP-2, Runx2, OCN or ALP. Conclusions: We indicate that ASCs may sense mechanical loading in a duration-dependent manner and cyclic tensile stretch may modulate the osteogenic differentiation of ASCs via the BMP-2 signalling pathway.